The THE CONSEQUENCE OF INTERNATIONAL LAW OF CHILDREN APPOINTMENT IN INDONESIA: THE CONSEQUENCE OF INTERNATIONAL LAW OF CHILDREN APPOINTMENT IN INDONESIA - Panjaitan, Hulman (Advances in Social Sciences Research Journal, 2020)
The adoption of children is nothing new in Indonesian society, including the adoption of international children, more specifically the adoption of children carried out by foreign citizens of Indonesian citizens. In practice, international appointments cause many legal problems, especially those related to the legal consequences. In this study normative juridical legal research methods are used with qualitative data analysis, which analyzes the data of the brother through existing legal materials based on applicable laws and regulations. At least as a result of international child adoption law, relating to aspects of citizenship, marriage guardianship and inheritance.